Fiscal dominance and the financial resource curse: The Paradoxes of Plenty and Banking - Collin Constantine (Latin American Journal of Central Banking (LAJCB), 2025)
This article models banking under the condition of fiscal dominance or monetised-fiscal deficits, and explains why resource-based economies experience a financial resource curse. The evidence shows that commodity price shocks engender premature deindustrialisation, reduce loan-deposit ratios and increase interest rate spreads, among other banking pathologies. The model demonstrates that commodity booms are accompanied by monetisation shocks as these explain accelerating bank deposits, interest costs, and persistent non-borrowed and non-remunerated reserves in the banking system. In turn, these lower the bank's profit margin (profitsdeposits), liquidity (bondsdeposits), and capital adequacy ratios (capitalloans). Therefore, the bank raises (lowers) its lending (deposit) rate to satisfy banking regulations without compromising profits. Thus, fiscal dominance reduces (raises) the loan-deposit ratio (interest rate spread). Moreover, the model shows that fiscal dominance increases the bank's share of consumer loans as a defensive measure against rising interest costs or non-bank competition, and triggers an unstable boom in property prices.
Keywords: E42; E43; E58; G21; H62; 330; Banking; Financial resource curse; Fiscal dominance; Monetised-fiscal deficits